Generation of memory B cells inside and outside germinal centers. Issue 5 (10th April 2014) - Takemori, Toshitada; Kaji, Tomohiro; Takahashi, Yoshimasa; Shimoda, Michiko; Rajewsky, Klaus
<x xml:space="preserve">Abstract</x> Germinal centers (GCs) are generally considered to be the sole site of memory B‐cell generation. However, recent studies demonstrate that memory B cells can also develop in response to a T‐cell dependent (TD) antigen before the onset, and independently of, the GC reaction. These two classes of memory cells persist equally over long periods of time and attain functional maturation through distinct but related transcriptional programs. Although the development of both memory B‐cell types requires classical T‐cell help, the generation of GC‐dependent memory B cells requires TFH‐cell help, while the generation of GC‐independent memory cells does not. These findings led to the conclusion that B‐cell memory is generated along two fundamentally distinct cellular differentiation pathways. In this review, we focus on the GC‐independent pathway of memory B‐cell development, and discuss how the unique features of memory B cells are maintained in the GC‐independent pathway.